RESEARCH TREND IN HADITH TEXT CRITICISM: A BIBLIOMETRIC ANALYSIS - Yaakob, Mohd Aizul; Baharudin, Muhammad Asyraf; Idris, Muhammad Ihsan; Abdullah, Mohammad Roshimi; Yasin, Mohammad Dhiya'ul Hafidh Fatah; Abdallah, Abdallah Saleh; Hasbulah, Muhamad Husni (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
This study explores the evolution and current research trends in Hadith text criticism through a bibliometric approach, addressing the limited understanding of its development in contemporary academic discourse despite its foundational role in classical Islamic scholarship. The primary objective is to map the scope, thematic orientation, and scholarly networks associated with research on the evaluation and authentication of Hadith texts. To achieve this, bibliographic data were extracted from the Scopus database using the keywords “hadith text” and “criticism,” resulting in a dataset of 149 journal articles published between 1970 and 2025. The data were cleaned and standardized using OpenRefine, analyzed for productivity trends and subject area distribution via the Scopus Analyzer, and visualized using VOSviewer to examine co-authorship networks, keyword co-occurrence, and citation patterns. The findings indicate that research in Hadith text criticism is predominantly situated within the disciplines of Social Sciences and Arts and Humanities. Core thematic areas include matn criticism, authentication, and fabrication, suggesting sustained scholarly engagement with traditional evaluative frameworks. In terms of geographical distribution, the majority of contributions originate from Southeast Asia and the Middle East, with an observable yet limited expansion in international collaborations. Overall, this study provides a comprehensive overview of the structural and thematic dimensions of Hadith criticism research, underscoring both the enduring relevance of classical methodologies and the growing incorporation of modern analytical tools.